Integrating Islamic Brand Experience and Digital Marketing Ethics to Foster Sustainable Loyalty in the Halal Coffee Industry - Maisyarah, Maisyarah; Iskandarini; Sulistya, Endang (Institut Agama Islam Negeri Parepare, 2026)
Purpose – This study aims to examine how the integration of sustainable Islamic marketing ethics through brand experience and social media strategies influences customer loyalty within the halal lifestyle industry, with a specific focus on the halal coffee sector in Indonesia. Method – A quantitative research design was employed using a survey-based approach, with data collected from consumers of halal coffee brands in Indonesia. The study applied Structural Equation Modeling (SEM) to analyze the relationships between multidimensional brand experience, Islamic ethical values embedded in social media marketing, customer engagement, trust, and sustainable customer loyalty. Findings – The results indicate that multidimensional brand experience—comprising sensory, affective, behavioral, and intellectual dimensions—significantly enhances customer engagement and trust when aligned with Islamic marketing ethics such as transparency (shiddiq), social responsibility, and Halalan-Thayyiban principles. Ethical social media content was found to strengthen emotional brand connections, which in turn plays a critical role in fostering sustainable customer loyalty. Practical implications – The findings suggest that KopiKudu can enhance customer loyalty by providing comprehensive brand experiences and implementing effective social media marketing strategies. Similar approaches can be applied by other coffee businesses to improve customer retention, engagement, and long-term commitment to the brand. Originality/value – This study contributes to the literature by integrating the effects of Brand Experience and Social Media Marketing on customer loyalty in the context of a local coffee shop. It highlights the importance of combining offline interactions with digital strategies to achieve sustainable customer loyalty